The Role of Social Media in Indonesia's Successful Implementation of the COVID-19 Vaccine Program in West Sumatera Province - Annisa Weriframayeni; Novia Amirah Azmi; Aqil Teguh Fathani (Universitas Indraprasta PGRI, 2022)
This study examines the COVID-19 vaccine campaign in Indonesia using a social media communication strategy. The social media communication strategy is evaluated based on the implementation of communication, resources, disposition, and bureaucratic organization. The research approach with the assistance of NVivo 12 Plus and data sources from the Twitter account of the Ministry of Health and West Sumatra Provincial Health Office as well as numerous works of literature. Generate important data and be able to analyze data. This study concludes that social media communication has been effective, with diverse information regarding the use of vaccines, the impact of their usage, good data openness, collaboration with government and corporate entities, and the implementation of various community support policies. Due to the cooperation between Youth and Sports, which is responsible for providing facilities and fostering religious peace, resources are effectively coordinated. The disposition indicator is a positive attitude and action that is consistently provided by medical staff to instill a sense of security and comfort. The success of vaccinations in Indonesia is determined by social media communication. Various socializations and education are offered efficiently and contribute to the implementation of the program. This study focuses solely on the role of social media contacts in the success of the COVID-19 vaccination program in Indonesia.